2021
DOI: 10.1186/s12931-021-01789-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between ICS use and risk of hyperglycemia in COPD patients: systematic review and meta-analysis

Abstract: Background The effect of inhaled corticosteroids (ICS) on risk of hyperglycemia in patients with chronic obstructive pulmonary disease (COPD) remains ambiguous. The aim of this study is to evaluate the association between ICS use and the incidence of hyperglycemia related adverse effects in COPD patients. Methods Medline/PubMed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov were searched from inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Blood tests Metabolic and endocrine panel: Oral corticosteroids are none for their dysregulating effects on glucose homeostasis [ 29 ]. This dysregulation was not seen in retrospective studies [ 30 ]. However, prospective studies comparing asthma patients with and without ICS have not been performed recently, as guidelines recommend ICS in all patients [ 31 – 33 ].…”
Section: Methodsmentioning
confidence: 85%
“…Blood tests Metabolic and endocrine panel: Oral corticosteroids are none for their dysregulating effects on glucose homeostasis [ 29 ]. This dysregulation was not seen in retrospective studies [ 30 ]. However, prospective studies comparing asthma patients with and without ICS have not been performed recently, as guidelines recommend ICS in all patients [ 31 – 33 ].…”
Section: Methodsmentioning
confidence: 85%
“… 140 However, a systematic review and meta-analysis has concluded that the use of ICS does not influence blood glucose and is not associated with the incidence of new-onset DM or the progression of diabetes in patients with COPD. 141 Furthermore, the influence of ICS on DM remains uncertain. 142 However, glycosylated hemoglobin levels increased considerably after 6 weeks of inhaled fluticasone therapy in a small prospective crossover study in individuals with established T2DM.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…The use of COPD medications is generally safe in patients with T2DM, but the effect of ICS on DM remains uncertain [53]. A systematic review and meta-analysis of 17 RCTs involving 43,430 subjects concluded that in patients with COPD, the use of ICS does not affect blood glucose levels and is not associated with the incidence of new-onset DM or its progression [54]. However, a small association between ICS use and the presence of T2DM with the occurrence of hyperglycaemia in susceptible individuals has been reported in the literature [6].…”
Section: Potential Impact On T2dm Of Drugs Used To Treat Copdmentioning
confidence: 99%